Determinants of competitiveness in the primary sector - Vergara-Narváez, Andrés (EFIM Ediciones, 2021)
With the exponential increase in the world population and its respective demand for food, research is needed to address the determinants of competitiveness in the primary sector, which will allow for a deeper understanding of competitiveness in this sector so that the challenges and challenges related to productivity improvements can be better addressed. Within this framework, a literature review is proposed to analyze precisely what are the determinants of competitiveness in this sector. Additionally, an analysis from the perspective of strategic typologies is proposed in order to give added value to this review. The results show that accumulated knowledge, efficiency, technological development and flexibility are some of the elements that generate competitive advantages for the primary sector.